Radiative corrections in elastic and deep-inelastic electron-proton scattering - Afanas’ev, A.V.; Akushevich, I.V.; Merenkov, N.P. (Вопросы атомной науки и техники, 2001)
The electron structure function method is applied to calculate model-independent radiative corrections to an asymmetry of electron-proton scattering. The representations for both spin-independent and spin-dependent parts of the cross section are derived. Master formulae take into account the leading correction in all orders and the main contribution of of the second order next-to-leading ones and have accuracy at the level of one per mille.